2009
DOI: 10.1590/s1806-37132009000900007
|View full text |Cite
|
Sign up to set email alerts
|

Comparação dos efeitos de duas técnicas fisioterapêuticas respiratórias em parâmetros cardiorrespiratórios de lactentes com bronquiolite viral aguda

Abstract: Objective: To compare the expiratory flow increase technique (EFIT) and vibration accompanied by postural drainage (PD) in terms of their effects on the heart rate (HR), respiratory rate (RR) and SpO 2 of infants with acute viral bronchiolitis (AVB). Methods: Infants with clinical and radiological diagnosis of AVB were analyzed. The HR, RR and SpO 2 were registered at four time points: prior to the procedure; and at 10, 30 and 60 min after the procedure. The patients were divided into three groups: submitted t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
9

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 12 publications
(19 reference statements)
0
9
0
9
Order By: Relevance
“…Diferentes estudos com manobras de higiene brônquica em diferentes populações, de prematuros a lactentes, mostram que as manobras de higienização brônquica não trazem alteração na função cárdica, especialmente na FC 7,8,9,10,11,20 . Os resultados aqui apresentados mostraram que tanto a técnica de vibrocompressão como o Pulsar ® são considerados técnicas seguras levando em conta o trabalho cardíaco, visto que os valores aqui estudados foram normais em todos os momentos do estudo.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Diferentes estudos com manobras de higiene brônquica em diferentes populações, de prematuros a lactentes, mostram que as manobras de higienização brônquica não trazem alteração na função cárdica, especialmente na FC 7,8,9,10,11,20 . Os resultados aqui apresentados mostraram que tanto a técnica de vibrocompressão como o Pulsar ® são considerados técnicas seguras levando em conta o trabalho cardíaco, visto que os valores aqui estudados foram normais em todos os momentos do estudo.…”
Section: Discussionunclassified
“…Em estudo realizado com recém-nascidos pré termos e de muito baixo peso, a vibração e a aspiração não geraram efeitos cardiopulmonares significativos 7 , assim como a manobra de aumento do fluxo expiratório (AFE) associada à vibração e drenagem postural em crianças com bronquiolite 8 . A tapotagem e a vibrocompressão em crianças asmáticas também não alteraram as condições cardiopulmonares no estudo de Lanza et al 9 .…”
Section: Introductionunclassified
“…Pupin et al [4], in a study of 81 infants with AVB, in order to compare the effects on physiological parameters in two respiratory therapy protocols, increased expiratory flow (IEF) and vibrocompression associated with postural drainage, decreased RR observed in infants undergoing physiotherapy techniques in relation the control group and the evolution of the HR showed an increase after 10 minutes after the procedure, the group submitted to the IEF protocol followed a decline at the end of the assessment, common to all groups.…”
Section: Discussionmentioning
confidence: 99%
“…The indication of RP in AVB remains controversial with regard to their effects on patients' clinical improvement and reduced hospitalization time. Some authors do not believe in the efficacy of performing RP in infants with AVB [4]. However, other authors found favorable results in physiologic parameters, mucocilicar increased clearance and improved lung auscultation through the application of respiratory therapy protocols [5-7].…”
Section: Introductionmentioning
confidence: 99%
“…O principal agente associado a esta condição clínica é o vírus sincicial respiratório (VSR), cujo ciclo de vida segue picos sazonais 1,2 . No Rio Grande do Sul, em um estudo de caso-controle, das 5.304 crianças acompanhadas 113 (2,1%) foram hospitalizadas por BVA no período pós-natal.…”
Section: Introductionunclassified